Local Branding: Imperative Strategy Towards Competitiveness of Sustainable Destinations Through the Role of Social Media - DC. Kuswardani; Nurhidayati Nurhidayati; Totok Wibisono; Aprih Santoso (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2023)
The aim of the research is to form the Competitiveness of Sustainable Destinations to realize tourism marketing through Local Branding. The variables tested are Local Branding and Destination Image. Social Media is expected to moderate the influence of Local Branding on the Competitiveness of Sustainable Destinations. The population is visitors to tourist attractions, while the sample is 152. Respondents are determined using the Proportionate Stratified Random Sampling technique. SEM as an analysis tool with the smartPLS.3.0 program application The results of the Sustainable Destination Competitiveness test results can be manifested through optimal management of Local Branding and Destination Image. Local Branding can be applied through Local Culture and Destination Image. Local Branding significantly affects the Competitiveness of Sustainable Destinations, while Local Culture significantly influences Local Branding. Destination Image significantly influences Local Branding and significantly influences the Competitiveness of Sustainable Destinations. Social Media is able to function as a pure moderator of the influence of Local Branding on the Competitiveness of Sustainable Tourism Destinations in Semarang City. The R - Square value in the Local Branding construct is 0.758536, meaning that Local Branding is influenced by Local Culture and Destination Image 75.85%. The Q Square value > 0 (0.575377) on the Local Branding variable indicates that the model has strong predictive relevance, meaning that the research model has relevance in predicting Local Culture and Destination Image with Local Branding in Tourism Objects. R-Square on the construct of Sustainable Destination Competitiveness 0.817528 means that the Competitiveness of Sustainable Destinations is influenced by Local Branding and Destination Image 81.75%. The Q Square value of 0.668352 (> 0) indicates that the model has strong predictive relevance, meaning that the research model has relevance in predicting Local Branding and Destination Image on the Competitiveness of Sustainable Tourism Destinations.